IMPLEMENTASI KEBIJAKAN PROGRAM AMBULANCE DESA POJA KECAMATAN SAPE KABUPATEN BIMA - Nirwana Nirwana; Taufik Irfadat (Jurnal Ilmu Administrasi Negara, 2022)
The purpose of this study was to explain "the implementation of the poja village ambulance program policy in sape sub-district, bima district. This research uses a qualitative approach method. data sources are obtained through interviews, observation, and documentation. the village ambulance program policy is one of the public service programs found in poja village, sape sub-district, bima district. Lack of socialization to the community is also one of the factors that cause policies that have been made to be less well implemented. factors like this are less considered by those who only provide what has become a village government program. based on the results of research that has been done, it can be seen that the operational implementation of the village ambulance is still not optimal. The commitment of the implementor in this case, namely the village government, has commitment and honesty and democratic siftat where the implementor is very upholding the commitment not to accept payments for people who use ambulances, and (3) the bureaucratic structure in this program is still said to be not good because it is related to the SOP.